Electroacupuncture Pretreatment Mitigates Myocardial Ischemia/Reperfusion Injury via XBP1/GRP78/Akt Pathway - Wang, Nisha; Ma, Jipeng; Ma, Yan; Lu, Linhe; Ma, Chao; Qin, Pei; Gao, Erhe; Zuo, Mingzhang; Yang, Jian; Yang, Lifang (Frontiers in Cardiovascular Medicine, 2021)
Myocardial ischemia/reperfusion injury is a common clinical problem and can result in severe cardiac dysfunction. Previous studies have demonstrated the protection of electroacupuncture against myocardial ischemia/reperfusion injury. However, the role of X-box binding protein I (XBP1) signaling pathway in the protection of electroacupuncture was still elusive. Thus, we designed this study and demonstrated that electroacupuncture significantly improved cardiac function during myocardial ischemia/reperfusion injury and reduced cardiac infarct size. Electroacupuncture treatment further inhibited cardiac injury manifested by the decrease of the activities of serum lactate dehydrogenase and creatine kinase-MB. The results also revealed that electroacupuncture elevated the expressions of XBP1, glucose-regulated protein 78 (GRP78), Akt, and Bcl-2 and decreased the Bax and cleaved Caspase 3 expressions. By using the inhibitor of XBP1 in vitro, the results revealed that suppression of XBP1 expression could markedly increase the activities of lactate dehydrogenase and creatine kinase-MB and cell apoptosis, thus exacerbating stimulated ischemia/reperfusion-induced H9c2 cell injury. Compared with stimulated ischemia/reperfusion group, inhibition of XBP1 inhibited the downstream GRP78 and Akt expressions during stimulated ischemia/reperfusion injury. Collectively, our data demonstrated that electroacupuncture treatment activated XBP1/GRP78/Akt signaling to protect hearts from myocardial ischemia/reperfusion injury. These findings revealed the underlying mechanisms of electroacupuncture protection against myocardial ischemia/reperfusion injury and may provide novel therapeutic targets for the clinical treatment of myocardial ischemia/reperfusion injury.